Step-By-Step Segmental Analysis of the Fetal Heart with an Uncommon Situs Anomaly - Ergani, Seval Yilmaz; Yılmaz, Osman (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Congenital heart diseases are the most common congenital anomalies during the fetal period. The diagnosis of complex congenital heart diseases in the fetal period is not always easy. While evaluating cardiac abnormalities, performing segmental analysis and step-by-step evaluation will facilitate the diagnosis of prenatal cardiac diseases. Here, we report a rare variant AV (atrioventricular) and VA (ventriculoarterial) discordance pattern detected in utero and identified based on step-by-step segmental analysis.
Keywords: Situs inversus; D-loop; D-transposition TGA; Segmental Analysis